Design for Improvement of COP from Waste Heat Utilization Through Air Conditioning System - Sabir, Saba; Pant, Hitesh; Kanojia, Nikhi; Rawat, Kuldeep (Journal of Graphic Era University, 2023)
Energy is in higher demand than ever before since there are an increasing number of applications for it; nevertheless, the existing sources are unable to supply it in sufficient quantities. Alternate energy sources should be utilized, and as a consequence, energy conservation should be achieved through the utilization of waste heat from air conditioning systems. The major objective of this piece is to make use of waste heat generated by residential air conditioning systems while simultaneously increasing the coefficient of performance (COP). In order to achieve this goal, an experimental setup is utilized. In this configuration, an indirect kind of heat recovery equipment is used, and a heat exchanger that converts heat from a refrigerant to water is positioned between the compressor and the condenser of the host refrigeration system. The hot refrigerant gas generated by the compressor is sent via one side of the heat exchanger, while water is forced through the other side. The temperature of the water is raised as a result of the heated refrigerant gas. Because of this, the system’s COP might potentially increase by up to 16%.